2017
DOI: 10.21149/7728
|View full text |Cite
|
Sign up to set email alerts
|

Factores socioeconómicos asociados con la compra ilegal de productos de tabaco en Panamá

Abstract: Objetivo. Caracterizar la compra ilegal de productos derivados del tabaco y su asociación con variables socio­demográficas y socioeconómicas. Material y métodos. La fuente de datos es la Encuesta Mundial de Tabaco en Adultos de 2013. Se caracterizó la compra ilícita mediante variables sociodemográficas (SOD) y socioeconómicas (SES). Se utilizaron modelos de regresión logística. Resultados. Se encontraron asociaciones de las variables SOD y SES con compra ilegal, particularmente en hombres; grupo etario de 15 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
1
1
Order By: Relevance
“…The proportion of illicit cigarettes identified in this study is higher than the one recently found for Colombia,15 though far below the level reported for Panama16 and Brazil 14 20. We do not have estimates for illicit cigarettes penetration in other areas of the country, but it could be expected that in border areas or those near duty free zones, the penetration could be higher, based on what was found in other Latin American countries, such as Colombia15 and Panama 16. Given that 40.5% of the national population lives in Metropolitan Santiago,21 it is very likely that the national total is close to what was reported here.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…The proportion of illicit cigarettes identified in this study is higher than the one recently found for Colombia,15 though far below the level reported for Panama16 and Brazil 14 20. We do not have estimates for illicit cigarettes penetration in other areas of the country, but it could be expected that in border areas or those near duty free zones, the penetration could be higher, based on what was found in other Latin American countries, such as Colombia15 and Panama 16. Given that 40.5% of the national population lives in Metropolitan Santiago,21 it is very likely that the national total is close to what was reported here.…”
Section: Resultscontrasting
confidence: 87%
“…Though typical illicit trade control measures are supply side oriented (eg, increasing penalties for contraband-related crimes, reducing or eliminating duty-free allowances, increasing controls at sensitive borders and implementing track and trace systems), identifying the socioeconomic variables associated with the purchase of illicit cigarettes may help authorities to understand relevant aspects of this phenomenon and help them to design more effective policies to control the illicit cigarette trade from the demand side. This follows similar studies conducted in the region, which also inquire about socioeconomic variables linked to illicit cigarette consumption 14–16. In this regard, the results obtained here can be compared with those obtained in similar countries.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation